Pengaruh Financial Knowledge, Self efficacy dan Social Support Terhadap Kesiapan Berwirausaha (Studi Pada Mahasiswa Kota Malang) - Amali, Yunila; Susyanti, Jeni; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The increase in the unemployment rate based on education level shows that the number of workers and the unemployment rate continue to increase every year, but the currently available workforce is not being absorbed well. Students must prepare themselves to get the skills needed by the world of work, after graduating they will have the ability to compete in the world of work. This research aims to find out how much influence Financial knowledge, Self-efficacy, and Social support have on entrepreneurial readiness for study in Malang City students. In this research, the type of research used is explanatory research. The sampling technique uses a nonprobability sampling technique with a purposive sampling type. Determining the sample size used the Malhotra formula and the results obtained were 90 Malang City student respondents. Data processing was carried out using a multiple linear analysis model with the help of SPSS version 25 data processing. The results of this research show that the financial knowledge variable has a significant effect on entrepreneurial readiness, the self-efficacy variable has a significant effect on entrepreneurial readiness and the social support variable has a significant effect on entrepreneurial readiness. Keywords: Financial Knowledge, Self Efficacy, Social Support, Entrepreneurial Readiness